State-of-the-art in fixture systems for the manufacture and assembly of rigid components: A review. (December 2017) - Gameros, A.; Lowth, S.; Axinte, D.; Nagy-Sochacki, A.; Craig, O.; Siller, H.R.
Abstract: Basic work holding devices (e.g. vices), fixtures and jigs are used to construct a critical interface between a workpiece and an end-effector. This interface performs two main functions: location of the workpiece in the Euclidean space and preservation of the workpiece position against any loads. Despite the critical nature of the part-machine interface, limited attention has been given to work holding systems in the academic community. In this respect, the main objective of this paper is to systematically review the field of fixture design, thus allowing the classification of fixturing systems to identify research trends and niches. This review is broken into four sections: (i) basics of fixturing and work holding; (ii) fixtures for single components. The classification of these systems is based on an evolutionary trend that allows to see how the development of technologies, such as additive manufacture, sensing technologies and actuation systems, affects fixture design; (iii) fixtures for multi-parts (both for batch production and assembly operations), with an emphasis on the unique challenges that arise from the assembling process; and (iv) conclusions, denoting various research trends/opportunities in the areas of fixture design and fixture instrumentation. Examples of these prospects includes the integration of fixtures with sensing technology (incentivise by the growth of industry 4.0) and the construction of truly new multi-part fixturing systems, rather than just the expansion of single component fixtures.